2017
DOI: 10.1590/18069657rbcs20160017
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality after Six Years of Paper Mill Industrial Wastewater Application

Abstract: ABSTRACT:The application of wastewater to irrigate soils may be an attractive option for paper mills, especially when the effluents can also provide nutrients to plants. Since there could be negative environmental effects, such activity must be preceded by a thorough evaluation of the consequences. The changes in soil quality of a Neossolo Flúvico Distrófico (Typic Udifluvent) were evaluated over a period of six years of irrigation with treated effluent from a wood pulp company. Although effluent application f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The application of wastewater will increase the OM contents in the soil which is considered a beneficial effect for soil [ 3 ]. The addition of organic matter into the soil through wastewater application improves the soil structure and the moisture content’s increased cation exchange capacity and helps to retain the metals and reduce their bioavailability and mobility and adds nutrients into the soils [ 108 , 109 , 110 ].…”
Section: The Effect Of Wastewater On the Physico-chemical Propertimentioning
confidence: 99%
“…The application of wastewater will increase the OM contents in the soil which is considered a beneficial effect for soil [ 3 ]. The addition of organic matter into the soil through wastewater application improves the soil structure and the moisture content’s increased cation exchange capacity and helps to retain the metals and reduce their bioavailability and mobility and adds nutrients into the soils [ 108 , 109 , 110 ].…”
Section: The Effect Of Wastewater On the Physico-chemical Propertimentioning
confidence: 99%
“…). The lowest saturated hydraulic conductivity of treated effluent soil was due to higher bulk density and lowest total porosity of the soil [25]. Infiltration rate was ranged from 6.6 to 52.5 cm h -1 with the mean value of 23.0 cm h -1 (Fig.…”
Section: Effect On Soil Physical Propertiesmentioning
confidence: 97%
“…The bulk density increased with distance from paper mill in the northeren, the western and eastern directions of nagaon pulp and paper mill of Assam, India [24]. The lowest total porosity in treated effluent mainly due to presents of higher micropore and lowest macropore within the soil [25].…”
Section: Effect On Soil Physical Propertiesmentioning
confidence: 99%
“…For irrigation purposes, Rezende et al ( 2010 ) reported that treated effluent can be used to irrigate eucalyptus plantations, which is the main raw material used in Brazilian pulp and paper mills. In turn, Almeida et al ( 2017 ) applied treated effluent on soil for 6 years, a period of a complete rotation of eucalyptus cultivation. It was noted that irrigation did not affect soil strength, hydraulic conductivity, and Ca, Mg, and organic carbon contents, while reducing mean aggregate size and increasing clay dispersion and pH.…”
Section: Reuse Of Treated Effluentsmentioning
confidence: 99%